CONTEMPORARY PEDAGOGY - Abdugani Abdumalikovich Tojiboev (PEDAGOGS, 2024)
This article discusses the rapidly evolving field of modern teaching. The work being done in the subject of pedagogy and its influence on education will be covered separately.